2015
DOI: 10.21071/az.v64i246.386
|View full text |Cite
|
Sign up to set email alerts
|

Análise financeira de sistemas de produção para novilhas em pastagem de Brachiaria brizantha

Abstract: The objective was to determine the economic feasibility and financial risk of different production systems for dairy heifers grazing on Xaraes pallisadgrass pasture, during the year, with roughage supplementation of sugarcane, during the autumn-winter and the supply of mineral mixture (commercial and selective). Each production system was characterized and quantified in accordance with the administrative and livestock realized during the period February 2006 to March 2008. The cash flows were constructed for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
2
0
5
Order By: Relevance
“…Our study concludes that market prices of inputs and products are the most important in defining the economic viability of enterprisesthe same conclusion that other authors have also found (Campos et al, 2014;Peres et al, 2015). It is, therefore, empirical evidence aligned with: i) economic theory, through which the market can be classified as very competitive and therefore with very low and often negative margins; and with ii) the sector agents' impressions that the rearing activity is perhaps the most sensitive in Brazilian beef cattle, since they imply relatively high investment and fixed capital, along with the low productivity (of calves) for income generation.…”
Section: Effect Of Overall Relative Price Level On the Npvsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study concludes that market prices of inputs and products are the most important in defining the economic viability of enterprisesthe same conclusion that other authors have also found (Campos et al, 2014;Peres et al, 2015). It is, therefore, empirical evidence aligned with: i) economic theory, through which the market can be classified as very competitive and therefore with very low and often negative margins; and with ii) the sector agents' impressions that the rearing activity is perhaps the most sensitive in Brazilian beef cattle, since they imply relatively high investment and fixed capital, along with the low productivity (of calves) for income generation.…”
Section: Effect Of Overall Relative Price Level On the Npvsupporting
confidence: 91%
“…From the economic perspective, our results follow those of Ferraz Junior (2016). For dairy cattle, it has been shown that adequate nutrition in the rearing stage is a key factor for increasing the environmental and financial sustainability of milk production systems (Margerison et al, 2013;Peres et al, 2015). Our study suggests the economic viability of balanced nutrition in enterprises dedicated to beef cattle raising.…”
Section: Effect Of the Nutritional Strategy On The Npvmentioning
confidence: 64%
See 1 more Smart Citation
“…Já a TIR, conceituada como a taxa de juros (desconto) que iguala o VPL do sistema de produção a zero, demonstra atratividade da implantação do sistema de produção. Assim, determinada atividade pecuária é atrativa se a TIR for superior ao custo de oportunidade de capital (Contador, 1988;Peres et al, 2015). Assim, é possível traçar uma análise bioeconômica consistente sobre a comparação de sistemas de produção, bem como as vantagens financeiras (lucro) na substituição de uma determinada tecnologia por outra, por exemplo, diferentes períodos de SPE.…”
Section: Introductionunclassified
“…Diversos estudos têm sido conduzidos na avaliação técnica e econômica de sistemas de produção aplicados ao agronegócio. Peres et al (2015) trabalharam com diferentes sistemas suplementação mineral aplicados a criação de novilhas leiteiras em pastagem de capim-Xaraés. Neste trabalho, os autores observaram que sistemas de produção em pastagens cultivadas foram viáveis financeiramente, a uma taxa mínima de atratividade de 14 % ao ano e, que o uso da suplementação mineral fornecida de forma adequada, melhorou os índices zootécnicos do rebanho e aumentou o retorno financeiro do capital investido.…”
Section: Introductionunclassified